Glycemic Variability and Vascular Complications in Patients with Type 2 Diabetes Mellitus - Caprnda, Martin; Mesarosova, Dasa; Ortega, Pablo Fabuel; Krahulec, Boris; Egom, Emmanuel; Rodrigo, Luis; Kruzliak, Peter; Mozos, Ioana; Gaspar, Ludovit (Folia medica, 2017)
BACKGROUND: Presence of macro- and microvascular complications in patients with diabetes mellitus (DM) is not only related to chronic hyperglycemia represented by glycated hemoglobin (HbA1c) but also to acute glycemic fluctuations (glycemic variability, GV). The association between GV and DM complications is not completely clear. Aim of our study was to evaluate GV by MAGE index in patients with type 2 DM and to verify association of MAGE index with presence of macro- and microvascular DM complications. METHODS: 99 patients with type 2 DM were included in the study. Every patient had done big glycemic profile, from which MAGE index was calculated. Anthropometric measurements, evaluation of HbA1c and fasting plasma glucose (FPG) and assessment for macrovascular (coronary artery disease - CAD; peripheral artery disease - PAD; cerebral stroke - CS) and microvascular (diabetic retinopathy - DR; nephropathy - DN; peripheral neuropathy - DPPN) DM complications were done. RESULTS: Average MAGE index value was 5.15 ± 2.88 mmol/l. We found no significant differences in MAGE index values in subgroups according to presence of neither CAD, CS, PAD nor DR, DN, DPPN. MAGE index value significantly positively correlated with FPG (p < 0.01) and HbA1c (p < 0.001) and negatively with weight (p < 0.05). CONCLUSION: In our study we failed to show association of MAGE index with presence of macrovascular and microvascular complications in patients with type 2 DM. However, this negative result does not necessarily disprove importance of glycemic variability in pathogenesis of diabetic complications.
Keywords: následné studie; Female; Severity of Illness Index; lidé středního věku; Follow-Up Studies; Risk Assessment; Age Distribution; věkové rozložení; diabetické angiopatie; Sex Distribution; kohortové studie; mužské pohlaví; Blood Glucose; Retrospective Studies; senioři nad 80 let; krevní glukóza; Diabetes Mellitus, Type 2; retrospektivní studie; glykemický index; Humans; Glycated Hemoglobin; incidence; stupeň závažnosti nemoci; Analysis of Variance; Diabetic Angiopathies; lidé; rozložení podle pohlaví; Middle Aged; glykovaný hemoglobin; Cohort Studies; Aged, 80 and over; senioři; ženské pohlaví; analýza rozptylu; hodnocení rizik; Aged; Glycemic Index; Male; diabetes mellitus 2. typu; Incidence